KONTRIBUSI PENGELOLAAN KEUANGAN DAN LITERASI KEUANGAN TERHADAP SIKAP KEUANGAN MAHASISWA DI RANGKASBITUNG - Furniawan; D. Muhamad Yamin (The Asia Pacific Journal Of Management Studies, 2025)
Financial attitude is an important factor in determining individual behavior in managing personal finances, especially among university students who are in the transition toward financial independence. This study aims to analyze the contribution of financial management and financial literacy to students’ financial attitudes in Rangkasbitung. This research employed a quantitative approach using a survey method involving university students in the Rangkasbitung area. Data were collected through structured questionnaires and analyzed using multiple linear regression with partial (t-test) and simultaneous (F-test) analyses. The results indicate that financial management contributes significantly to students’ financial attitudes. In addition, financial literacy also makes a significant contribution to shaping financial attitudes. Simultaneously, financial management and financial literacy jointly contribute significantly to students’ financial attitudes. These findings confirm that students’ financial attitudes are shaped by the synergy between practical financial management skills and adequate financial knowledge. Therefore, integrated efforts through financial literacy education and the development of sound financial management practices are necessary to foster healthy and sustainable financial attitudes among students.